1993
DOI: 10.1007/bf00231878
|View full text |Cite
|
Sign up to set email alerts
|

Exocytotic fusion pores exhibit semi-stable states

Abstract: Rapid-freezing/freeze-fracture electron microscopy and whole-cell capacitance techniques were used to study degranulation in peritoneal mast cells of the rat and the mutant beige mouse. These studies allowed us to create a time-resolved picture for fusion pore formation. After stimulation, a dimple in the plasma membrane formed a small contact area with the secretory granule membrane. Within this zone of apposition no ordered proteinaceous specializations were seen. Electrophysiological technique measured a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 27 publications
5
88
0
Order By: Relevance
“…The kinetics of exocytosis are slow (Nemoto et al, 2001;Thorn et al, 2004), and we have proposed that endocytosis may occur by recovery of granule membrane in a piecemeal process . Here, we show that the fusion pore formed by the zymogen granule is one of the largest pores identified (Curran et al, 1993;Melikyan et al, 1995) (we estimate a pore diameter of between 29 and 55 nm), and yet it is capable of closing. We provide evidence that this closure is likely a prelude to endocytosis and that it occurs after the majority of granule contents are lost.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The kinetics of exocytosis are slow (Nemoto et al, 2001;Thorn et al, 2004), and we have proposed that endocytosis may occur by recovery of granule membrane in a piecemeal process . Here, we show that the fusion pore formed by the zymogen granule is one of the largest pores identified (Curran et al, 1993;Melikyan et al, 1995) (we estimate a pore diameter of between 29 and 55 nm), and yet it is capable of closing. We provide evidence that this closure is likely a prelude to endocytosis and that it occurs after the majority of granule contents are lost.…”
Section: Introductionmentioning
confidence: 74%
“…In other systems, there is evidence that the fusion pore is dynamic, changing over time and existing in one of three distinct states (Fernandez et al, 1984, Spruce et al, 1990Curran et al, 1993;Wang et al, 2001). It is first observed as a small pore with a conductance similar to that of an ion channel (Zimmerberg et al, 1987;Spruce et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, release continues afterward for many tens to hundreds of milliseconds. The initial opening of the fusion pore has been monitored by capacitance; the pore flickers open and closed for 10-15,000 ms before it starts to expand (27)(28)(29)(30). The pore may continue to widen for hundreds of milliseconds before the vesicle is flattened into the plasma membrane.…”
Section: N-terminal Domain Of Syntaxin Has Inhibitory Effect On Snarementioning
confidence: 99%
“…The rate of fusion pore expansion of phase I was around 30 pS ms-I. In addition to this initial phase, which has been studied extensively (Breckenridge & Almers, 1987;Alvarez de Toledo & Fernandez, 1988;Curran et al 1993), we could distinguish two more stages clearly identified by their rate of expansion. An abrupt opening of the pore, phase H, had expansion rates as high as 3000 pS ms-I.…”
Section: If Physiologisches Institut Der Universitiit Des 8aarlandesmentioning
confidence: 63%